Reproduction and conservation of the Magdalena River turtle (Podocnemis lewyana) in the Claro Cocorná Sur River, Colombia (2014)
ABSTRACT: The Magdalena River Turtle, Podocnemis lewyana, is an endangered and endemic turtle from Colombia. Among the most important information needed to conserve endangered species is to identify, monitor, and protect the sites used by the species to reproduce and grow. In this study we report, for the first time, the reproductive output and the nesting beaches of P. lewyana in the Claro Cocorná Sur River, a tributary of the Magdalena River drainage. We systematically examined a river transect of 8 km with 14 sandy beaches during two nesting seasons in one year. We recorded a yearly production of 47 clutches, 957 eggs, and two preferred nesting beaches: Alto Bonito with 51 %, and Bélgica with 28.3 % of this reproductive output. AAFUVER, a community-based organization, has led a headstarting program since 2010 to decrease in-situ egg mortality due to predation on nesting beaches. AAFUVER collects and incubates the eggs ex-situ, raises the hatchlings for one to five months and then releases them into the same river. To understand potential effects of such egg manipulation, we monitored and compared in-situ and ex-situ incubation temperatures. We found ex- situ temperatures below the pivotal temperature known for P. lewyana and below the temperatures in nesting beaches. Finally, we monitored hatchlings growth under AAFUVER captive conditions, and found that hatchlings duplicated their body mass during the first three months of age. Egg weight was strongly associated to body weight at hatching, however this association is lost by the third month of age. We strongly encourage supporting this community-based conservation program, andthe protection of the Claro Cocorná Sur River as an important nesting and growth habitat for the conservation of P. lewyana.